Local decline and populism - Thiemo Fetzer; Jacob Edenhofer; Prashant Garg (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Support for right-wing populist parties is characterised by considerable regional heterogeneity and especially concentrated in regions that have experienced economic decline. It remains unclear, however, whether the spatial externalities of local decline, including homelessness and crime, boost support for populist parties, even among those not directly affected by such decline. In this paper, we contribute to filling this gap in two ways. First, we gather novel data on a particularly visible form of local decline, high-street vacancies, that comprise 83,000 premises in England and Wales. Second, we investigate the influence of local decline on support for the right-wing populist UK Independence Party (UKIP) between 2009 and 2019. We find a significant positive association between high-street vacancy rates and UKIP support. These results enhance our understanding of how changes in the lived environment shape political preferences and behaviour, particularly in relation to right-wing populism.
Keywords: D72; R11; R12; R23; 330; Local Economic Conditions; Populism; High-street Vacancies; Spatial Externalities